New Gold(I) Complexes as Potential Precursors for Gas-Assisted Methods: Structure, Volatility, Thermal Stability, and Electron Sensitivity - Aleksandra Butrymowicz-Kubiak; Tadeusz M. Muzioł; Piotr Madajski; Iwona B. Szymańska (Molecules)
We report the synthesis and characterization of new, user-friendly gold(I) [Au4(μ-(NH)2CC2F5)4]n coordination polymer and [Au2Cl2(NH2(NH=)CC2F5)2]n complex. These compounds were investigated for potential application as precursors in chemical vapor deposition (CVD) and focused electron/ion beam-induced deposition (FEBID/FIBID), which are additive methods to produce nanomaterials. Single-crystal X-ray diffraction, elemental analysis, and infrared spectroscopy were used to determine the complexes’ composition and structure. We studied their thermal stability and volatility using thermal analysis and variable-temperature infrared spectroscopy (VT IR) and by conducting sublimation experiments. The gold(I) amidinate [Au2(μ-(NH)2CC2F5)2]n sublimates at 413 K under 10−2 mbar pressure. The electron-induced decomposition of the complexes’ molecules in the gas phase and of their thin layers on silicon substrates was analyzed using electron impact mass spectrometry (EI MS) and microscopy studies (SEM/EDX), respectively, to provide insights for FEBID and FIBID precursor design. The [Au2Cl2(NH2(NH=)CC2F5)2]n hydrogen chloride molecules evolved during heating, with the formation of gold(I) amidinate. The obtained results revealed that the new gold(I) amidinate may be a promising source of metal for nanomaterial fabrication by gas-assisted methods.